2014
DOI: 10.7314/apjcp.2014.15.21.9137
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Clinicopathological Contribution of DcR3 in Bladder Urothelial Carcinoma Tissues

Abstract: Asian Pac J Cancer Prev, 15 (21), 9137-9142 IntroductionBladder urothelial carcinoma (BUC) is the fifth most common cancer worldwide, with an estimated incidence of 73, 510 cases and 14, 880 deaths in the United States in 2012. In China, the morbidity of urothelial carcinoma is 6.61/100,000, ranked the ninth in all malignant tumors (O'Keeffe et al., 2008;Yang et al., 2011;Siegel et al., 2012;Bracha et al., 2014). The decoy receptor 3 (DcR3), locating on chromosome 20q13, is a member of the tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Dysregulated DcR3 expression plays an important role in tumorigenesis, metastasis and immune suppression in pancreatic head cancer [6], breast cancer [7], bladder urothelial carcinoma [8], nasopharyngeal carcinoma [9], renal carcinoma [10], glioma [11] and hepatocellular carcinoma [12, 13]. However, the contribution of DcR3 to CRC and the molecular basis for this contribution have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulated DcR3 expression plays an important role in tumorigenesis, metastasis and immune suppression in pancreatic head cancer [6], breast cancer [7], bladder urothelial carcinoma [8], nasopharyngeal carcinoma [9], renal carcinoma [10], glioma [11] and hepatocellular carcinoma [12, 13]. However, the contribution of DcR3 to CRC and the molecular basis for this contribution have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…DcR3/TNFRSF6B also protects against apoptosis because it can neutralize the cytotoxic ligands TNFS14/LIGHT, TNFSF15 and TNFSF6/FASL. Higher DcR3 expression was related to the status of invasion, lymph node metastasis and recurrence in bladder urothelial carcinoma [52]. Overexpression of DcR3 was found in bladder urothelial carcinomas and cell lines, with significant elevation as compared to normal bladder tissues and negatively correlated with caspase-3 and positively associated with Bcl-2, VEGF, and p53.…”
Section: Tumor Necrosis Factor-related Decoy Receptorsmentioning
confidence: 89%
“…DcR3 is expressed highly in a wide variety of tumors such as gastric cancer,28 colon cancer,20 breast cancer,29 bladder cancer,30 and liver cancer 31. It has been demonstrated that overexpression of DcR3 was correlated with tumor differentiation, lymph node metastasis, as well as TNM stage and prognosis,32 while downregulation of DcR3 could inhibit the proliferation and migration of tumor cells and increase the apoptosis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%